Microstructure and wear characteristics of a hypereutectic Al-Si alloy produced by spray deposition - Srivastava V.C.; Mandal R.K.; Ramchandra C.; Chatterjee B.; Ojha S.N. (My University, 2025)
The spray deposition of a commercial hypereutectic Al-Si allloy under various processing conditions has been investigated. The microstructure and wear properties of the alloy produced by spray deposition process are compared with those produced by conventional casting method. The microstructure of the spray deposited material showed considerable refinement of the primary Si phase and modification of its eutectic morphology. The primary Si phase varied from 2 to 5 μm in spray deposits against 70 to 130 μm in that of the as cast alloy. Electron Probe Microanalysis indicated considerable chemical homogeneity in the spray deposited alloy. In contrast, large segregation of alloying elements were observed in the as cast alloy. The results of X-ray diffraction analysis showed variation in lattice parameter of oversprayed powders as a function of their particle size indicating difference in cooling rate during solidification of droplets. The alloy produced by spray casting revealed its relatively low wear rate compared to that of the as cast alloy under a range of applied load from 6-10 kg and sliding velocity from 0.3-1.5 ms-1. This behavior is discussed in the light of microstructural features produced during spray casting.